2020
DOI: 10.1556/2006.2020.00046
|View full text |Cite
|
Sign up to set email alerts
|

The prospective effect of purpose in life on gambling disorder and psychological flourishing among university students

Abstract: Background and aimsGambling disorder (GD) is a mental disorder with a relatively higher prevalence in university students compared to adolescents and adults. Its reciprocity with mental being indicators, such as psychological flourishing, would be expected, but prior to this study had not yet been empirically examined. In addition, the predictive value of purpose in life (PIL) on university students' GD and psychological flourishing also remained unknown. This 1-year longitudinal study was the first to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 90 publications
1
10
0
1
Order By: Relevance
“…These findings are consistent with those in other studies that show that the high meaning of PP is linked to a lower consumption of alcohol [23,[31][32][33] and marijuana [24]. Indirect evidence of this is also provided by recent studies that suggest that meaning or purpose in life acts as a protective factor against a variety of behavioral additions such as Internet addiction [70] or gambling disorders [71,72].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with those in other studies that show that the high meaning of PP is linked to a lower consumption of alcohol [23,[31][32][33] and marijuana [24]. Indirect evidence of this is also provided by recent studies that suggest that meaning or purpose in life acts as a protective factor against a variety of behavioral additions such as Internet addiction [70] or gambling disorders [71,72].…”
Section: Discussionsupporting
confidence: 90%
“…14 In China, suicide is the leading cause of death for young people, 15,16 and previous studies have suggested that positive psychological factors, such as hope, purpose of life, flourishing and belief in change, are factors that protect against self-harm and suicidal behaviour among university students. 17,18 Conversely, mental health symptoms are closely related to social withdrawal, self-harm and suicidal behaviours. 19 Furthermore, prolonged social withdrawal among young people is increasing in China.…”
Section: Mental Well-being Of University Students In Chinamentioning
confidence: 99%
“…Searching for meaning in life is positively related to addictive behaviors, but finding meaning and purpose in life is important factor for recovery of addicted individuals. For example, difficulties with finding meaning and purpose in life are related to alcohol and drug abuse (Crumbaugh and Maholick 1964;Harlow et al 1986;Newcomb and Harlow 1986;Nicholson et al 1994), sedative use (Koushede and Holstein 2009), smartphone addiction (Çevik et al 2020), and gambling (Zhang et al 2020). However, finding meaning and purpose in life is an important factor in the process of recovery from alcoholism (Gutierrez 2019;Lyons et al 2011;Krentzman et al 2017), as the core of spiritual transformation is based on the social learning that has taken place among AA participants (Lyons et al 2010).…”
Section: Indirect Relationship Between Spirituality and Wellbeing Through Meaning In Lifementioning
confidence: 99%